1999
DOI: 10.1090/s0894-0347-99-00290-8
|View full text |Cite
|
Sign up to set email alerts
|

Well-posedness in Sobolev spaces of the full water wave problem in 3-D

Abstract: We consider the motion of the interface of a 3-D inviscid, incompressible, irrotational water wave, with air region above water region and surface tension zero. We prove that the motion of the interface of the water wave is not subject to Taylor instability, as long as the interface separates the whole 3-D space into two simply connected C 2 C^{2} regions. We prove further the existence and uniqueness of solutions of the full 3-D water wave problem, locally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
361
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(367 citation statements)
references
References 20 publications
5
361
0
1
Order By: Relevance
“…The first breakthrough in solving the well posedness for general data came in the work of S. J. Wu [Wu97], [Wu99] who solved the problem in 2 and 3 dimensions. There are many other works on local well posedness.…”
Section: Introductionmentioning
confidence: 99%
“…The first breakthrough in solving the well posedness for general data came in the work of S. J. Wu [Wu97], [Wu99] who solved the problem in 2 and 3 dimensions. There are many other works on local well posedness.…”
Section: Introductionmentioning
confidence: 99%
“…As proved by Wu [32,33], she showed that, as long as the interface is non-self-intersecting, the Taylor sign condition @p=@n c 0 > 0 always holds for the n-dimensional infinite-depth gravity water waves system, where n 2 (n D 2; 3 for physical relevance). Hence the Taylor instability is not an issue.…”
Section: Previous Resultsmentioning
confidence: 97%
“…The recent work has depended on establishing the well-posedness of the water wave equations, pioneered by Wu [44,45]. See AlvarezSamaniego & Lannes [46] and their references for more information about the mathematically rigorous validity of these models as approximations of the equations of (inviscid and irrotational) water waves.…”
Section: Appendix a (A) Mathematical Models Of Water Wavesmentioning
confidence: 99%